A short guide to operational risk - Tattam, David (Short guides to business risk series., 2011)
A Short Guide to Operational Risk provides you with a basic yet comprehensive overview of the nature of operational risk in organizations. It is a book to be read and shared at all levels of the organization; it offers a common understanding and language of risk that will provide individual readers with the basis to develop risk management skills, appropriate to their role in the business.